Regulation of Ca(V)2 calcium channels by G protein coupled receptors - Zamponi, Gerald W. (2012)
Voltage gated calcium channels (Ca(2+) channels) are key mediators of depolarization induced calcium influx into excitable cells, and thereby play pivotal roles in a wide array of physiological responses. This review focuses on the inhibition of Ca(V)2 (N- and P/Q-type) Ca(2+)-channels by G protein coupled receptors (GPCRs), which exerts important autocrine/paracrine control over synaptic transmission and neuroendocrine secretion. Voltage-dependent inhibition is the most widespread mechanism, and involves direct binding of the G protein βγ dimer (Gβγ) to the α1 subunit of Ca(V)2 channels. GPCRs can also recruit several other distinct mechanisms including phosphorylation, lipid signaling pathways, and channel trafficking that result in voltage-independent inhibition. Current knowledge of Gβγ-mediated inhibition is reviewed, including the molecular interactions involved, determinants of voltage-dependence, and crosstalk with other cell signaling pathways. A summary of recent developments in understanding the voltage-independent mechanisms prominent in sympathetic and sensory neurons is also included.